2008
DOI: 10.1007/s11427-008-0028-6
|View full text |Cite
|
Sign up to set email alerts
|

Leaf surface factors of transgenic Bt cotton associated with the feeding behaviors of cotton aphids: A case study on non-target effects

Abstract: The present paper reports case study results of the risk assessment of transgenic Bt cotton on a non-target pest, cotton aphid, Aphis gossypii. Several types of techniques, i.e., electrical penetration graph (EPG), light and electron microscopy, bioassays and chemical analysis, were applied to investigate physical and chemical leaf factors of 2 transgenic Bt cotton lines (GK12 and GK19) and their parental non-Bt cotton line (Simian3) associated with searching and feeding behaviors of cotton aphids on leaves or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…The latter effect was also found in our study. While a previous study reported differences in the trichome density between Bt and non- Bt cotton plants [33], this could not be confirmed for the three cotton varieties used in our study. It was noticeable, though, that the trichome density of Bt plants showed considerably less variation as compared to non- Bt plants.…”
Section: Discussioncontrasting
confidence: 97%
“…The latter effect was also found in our study. While a previous study reported differences in the trichome density between Bt and non- Bt cotton plants [33], this could not be confirmed for the three cotton varieties used in our study. It was noticeable, though, that the trichome density of Bt plants showed considerably less variation as compared to non- Bt plants.…”
Section: Discussioncontrasting
confidence: 97%
“…The densities of trichome and sclereid measurements at the surface of rough rice were carried out under a scanning electron microscope (SEM) (Tokyo, Japan) (Xue et al, 2008). Thirty samples were examined and the results were calculated as trichome and sclereid density per 1 mm 2 .…”
Section: Trichome and Sclereid Densitymentioning
confidence: 99%
“…The seeds of the two genotypes were provided by colleagues from the Biotechnology Research Center of CAAS. Cotton genotypes exhibited marked differences in leaf trichome density (Xue et al, 2008), Bt toxin content (Zhang et al, 2006) and associated resistance to lepidopteran species.…”
Section: Cotton Genotypesmentioning
confidence: 99%
“…However, the effects of mixed-row intercropping showed a significant variation among years and within genotypes. Xue et al (2008) stated that the outbreak of cotton aphid was more frequently observed in transgenic Bt cotton because the lower leaf trichome density of transgenic Bt cotton facilitated aphid feeding compared with conventional non-Bt cultivars. Accordingly, we would have expected an intermediate cotton aphid population in mixture plots, with the highest densities in Bt plots and the lowest densities in non-Bt plots.…”
Section: Impact Of Row-mixture As a Bt Resistance Management Approachmentioning
confidence: 99%